Multi-optimization of a spherical mechanism for minimally invasive surgery - Niu, Guo-jun; Pan, Bo; Zhang, Fu-hai; Feng, Hai-bo; Fu, Yi-li (Journal of Central South University, 2017)
In order to obtain the remote center motion (RCM) mechanism with better performance indexes and avoid the collision of multi-manipulators in minimally invasive surgery (MIS), a novel multi-objective optimization model was presented. There were two optimization objectives: a global kinematic performance index and a comprehensive stiffness index. Other indexes to characterize the design requirements such as collision probability, workspace, mechanism parameter, mass, and wall thickness were considered as constraints. Angles between two adjacent joints and cross-section dimensions of links were chosen as the design variables. The non-dominated sorting genetic algorithm II (NSGA-II) was adopted to solve the complex multi-objective optimization problem. Then, a 3-degree of freedom (DoF) MIS robotic prototype based on optimization results has been built up. The experiments to test the spatial position change of the remote center point and to test the absolute position accuracy and repetitive position accuracy of the MIS robot were achieved, and the experimental results meet the requirements of MIS.